Changing spaces of political encounter and the rise of anti-politics: Evidence from Mass Observation's General Election diaries. (January 2017) - Clarke, Nick; Jennings, Will; Moss, Jonathan; Stoker, Gerry
Abstract: Negativity towards the institutions of formal politics is currently a concern across much of the democratic world. It is generally agreed that such negativity increased among British citizens during the second half of the twentieth century. In this paper, we analyse a novel dataset not previously used to study this topic: Mass Observation's General Election diaries. Since diarists wrote mostly about politicians, political campaigns, and associated media coverage, we ask specifically what the diaries can tell us about increased negativity towards politicians and its relationship to developments in political communication. We take a postholing approach to sampling of the diaries, enabling comparative-static analysis between the middle and end of the twentieth century. We view the diaries in a geographical framework derived from contextual theories of social action. This gives us a focus on spaces of political encounter, modes of political interaction, performances by politicians, and judgements by citizens. We argue that prominent spaces of political encounter changed over the period from long radio speeches and rowdy political meetings to televised debates and associated expert commentary. We demonstrate how these latter settings for political interaction afforded less opportunity for politicians to perform virtues to citizens, and for citizens to calibrate judgements of politicians. Highlights: Analyses a novel dataset not previously used to study the topic of anti-politics: Mass Observation's General Election diaries. Helps us to understand more about anti-politician sentiment in Britain and its political communication explanations. Argues that prominent spaces of political encounter changed over the second half of the twentieth century from long radio speeches and rowdy political meetings to televised debates and associated expert commentary. Demonstrates how these latter settings for political interaction afforded less opportunity for politicians to perform virtues to citizens, and for citizens to calibrate judgements of politicians.